2021
DOI: 10.3748/wjg.v27.i21.2895
|View full text |Cite
|
Sign up to set email alerts
|

Clinicopathological characteristics and prognosis of 232 patients with poorly differentiated gastric neuroendocrine neoplasms

Abstract: BACKGROUND Poorly differentiated gastric neuroendocrine neoplasms (PDGNENs) include gastric neuroendocrine carcinoma (NEC) and mixed adenoneuroendocrine carcinoma, which are highly malignant and rare tumors, and their incidence has increased over the past few decades. However, the clinicopathological features and outcomes of patients with PDGNENs have not been completely elucidated. AIM To investigate the clinicopathological characteristics and prognostic factors of pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 27 publications
1
7
0
Order By: Relevance
“…7 The clinical manifestations engendered by cancer metastasis were abdominal distension and belly pain. 8 A previous study has reported that the prognosis of GNEC was worse than that of gastric adenocarcinoma. 9 Tumor size, stage, location, and treatment were significantly associated with the prognosis of GNEC patients.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…7 The clinical manifestations engendered by cancer metastasis were abdominal distension and belly pain. 8 A previous study has reported that the prognosis of GNEC was worse than that of gastric adenocarcinoma. 9 Tumor size, stage, location, and treatment were significantly associated with the prognosis of GNEC patients.…”
Section: Introductionmentioning
confidence: 98%
“…9 Tumor size, stage, location, and treatment were significantly associated with the prognosis of GNEC patients. 8 However, the survival differences between GNEC and IGC have not been clarified yet. Understanding these differences is important for prognosis evaluation and tailored treatment strategies.…”
Section: Introductionmentioning
confidence: 99%
“…Because LCNEC can arise from adenocarcinoma, it usually contains an adenocarcinoma component and thus has a high risk of being misdiagnosed as adenocarcinoma, which can hinder the pathological diagnosis. 22 The pathology in the current patient accordingly revealed an adenocarcinoma component, highlighting the need to understand the morphological and pathological characteristics of GLCNEC. Our patient had a solitary, metachronous (8 months after gastrectomy) tumor less than 4 cm in diameter and underwent successful radical resection.…”
Section: Discussionmentioning
confidence: 98%
“…Early G-NENs have weak invasiveness, a low malignancy rate and a good prognosis, with an OS as high as 100% in 3 years [39] . Hu et al [40] showed that for patients with G-NENs, the MST exceeded 150 months, and the total OS was 81.1% in 5 years.…”
Section: Discussionmentioning
confidence: 99%